Social Factors Affecting Performance of Women Enterprenuers: A Case of Small and Medium Enterprises in Ruiru,Kiambu County Kenya - Maina, Everlyne Vunyifwa (Pan Africa Christian University, 2017)
The aim of this study was to establish social factors influencing the performance of women entrepreneurs in Ruiru Town in Kenya. Entrepreneurs are the most important actors of the economy of any country. Globally they are the inventors of new products and services; they create new jobs and wealth. Entrepreneurship has been a male dominated phenomenon but the situation has been changing with time. Women being the backbone of economies in developing countries and specifically in Kenya, play a significant role to ensure their families are “well up". The research focused on the women entrepreneurs and their characteristics. The social factors are cultural values, attitude of the women entrepreneurs, and the role of skills in the women entrepreneurs. The study determined how social factor influenced the women entrepreneurs' performance. The researcher worked with a case of twenty five women entrepreneurs from Ruiru town as the sample study. The sample was in five different strata and each stratum had five women which they were selected randomly. The researcher focused on the cultural values, attitude of the entrepreneur and social role expectations as the independent variables of the conceptual frame work as the social factors affecting the women entrepreneurs. The performance of the women entrepreneur was the dependent variables. The performance variables were profitability, sales/volumes, increase of customers, asset growth, business expansion and increase of staff. Descriptive survey was the data collection method. This method of research was preferred because the researcher was able to collect data which was used to answer questions concerning the current status of the subject of study. The researcher used a questionnaire with both closed and open-ended questions for data collection. The social factors that influence women entrepreneurs such as education are paramount. Women who are degree holders venture in entrepreneurship are few. Entrepreneurial skills and management skills influence the woman entrepreneur performance as a leader to a very high extent. Gender as a social factor did not have a high influence on the performance of the women entrepreneurs. Social role expectation and cultural values had influence to the performance while positive attitude had a positive influence on the performance of the women entrepreneurs. From the findings, skills and education have a high extent of influence on the performance of women entrepreneurs as leaders. Therefore women need to be equipped through training of entrepreneurial skills and leadership skills. Entrepreneurship training should also be made compulsory in higher learning institutions. Empowering women entrepreneurs can create employment.
Keywords: Women Enterpreneurship,The Role of Skills in Woman Enterpreneur,The Attitude of The Women Enterpreneurs